Knockdown of Oligosaccharyltransferase Subunit Ribophorin 1 Induces Endoplasmic-Reticulum-Stress-Dependent Cell Apoptosis in Breast Cancer - Ding, Jiajun; Xu, Jiahui; Deng, Qiaodan; Ma, Wei; Zhang, Rui; He, Xueyan; Liu, Suling; Zhang, Lixing (Frontiers in Oncology, 2021)
Ribophorin 1 (RPN1) is a major part of Oligosaccharyltransferase (OST) complex, which is important in the N-linked glycosylation. Though it has been verified that the abnormality of glycosylation is closely related to the development of breast cancer, the specific role that RPN1 plays in breast cancer remains unknown. In this study, we used the public databases to investigate the relationship between the expression levels of OST subunits and the prognosis of breast cancer. Then, the function of RPN1 in breast cancer and the potential mechanisms were investigated. Our study showed that the expression of several OST subunits like RPN1, RPN2, STT3A STT3B and DDOST were upregulated in breast cancer. The protein expression level of RPN1 was also upregulated in breast cancer. Higher expression of RPN1 was associated with worse clinical characters and poorer prognosis. Furthermore, knockdown of RPN1 suppressed the growth and invasion of breast cancer cells in vitro and could induce cell apoptosis triggered by endoplasmic reticulum stress. Our results identified the oncogenic function of OST subunit RPN1 in breast cancer and RPN1 might be a potential biomarker and therapeutic target for breast cancer.